With Medicine in Mind? Exploring the Relevance of Having Recreational Experience When Becoming a Medicinal Cannabis User. (June 2022) - Kvamme, Sinikka L.
Background: Beyond the legal use of medical cannabis in Denmark for selected patient groups, a large unregulated use of medicinal (non-prescribed) cannabis occurs. However, little is known about the paths to becoming a medicinal cannabis user and the role that previous recreational experience plays in this process. Aim: Inspired by Becker's social learning approach to becoming a cannabis user, this study explores sources of inspiration for medicinal cannabis use, the social control factors related to use, and the relevance of recreational experience (RE) with cannabis. Methods: An anonymous survey was made available online to a convenience sample of 2, 281 adults (≥18 years) who self-medicate with non-prescribed cannabis. Logistic regression analysis compared users with no RE (46.1%) to users with occasional RE (27.4%) and regular RE (26.5%) in terms of user characteristics, initiation of medicinal use, and experiences with social control factors. Results: Compared to users with RE, users with no RE were significantly more likely to be women, older, more frequent users, and to treat somatic conditions and use low potency CBD-oil. Users with no RE were more likely to rely on social networks for information on medicinal cannabis, use online sources for supply, and find supply stable. Moreover, users with no RE were less likely to keep use secret and find use problematic. Also, when medicinal use develops on a gradual transition from recreational use it is associated with increased odds of treating mental health conditions and with use of smoking as form of intake. Conclusion: The heterogeneity among medicinal cannabis users in Denmark, in terms of demographics, motives for use, and patterns of use, is related to the level of previous recreational experience and to whether medicinal use developed on a gradual transition from recreational use.